When ‘Non-Instructional’ Librarians Teach: Navigating Faculty Status and Teaching Portfolios - Cooney, Cailean; Clyde, Wanett; Karpinski, Kel R.; Tidal, Junior; Johnson, Nanette (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
This article shares individual and collective experiences from five faculty ranked librarians with roles outside of formal instruction who are employed at an academic institution in the United States, and their approach to developing and embracing a teacher identity in the context of their professional trajectory. The article explores how the authors prepared to be evaluated against traditional classroom teaching for promotion by forming a cohort-based group to support “non-instructional” librarians to create a teaching portfolio, and how they approached teaching from liminal and, at times, tenuous positions and career stages. Authors conclude that the process challenged and expanded their perceptions of librarians and their own roles by revealing essential teaching functions performed regularly, regardless of their “non-teaching” title. Furthermore, developing a teaching portfolio has additional value in supporting the profession at large and demonstrating the essential role of the library at higher education institutions.